2004
DOI: 10.1074/jbc.m401532200
|View full text |Cite
|
Sign up to set email alerts
|

A Platelet Secretion Pathway Mediated by cGMP-dependent Protein Kinase

Abstract: Platelet secretion (exocytosis) is critical in amplifying platelet activation, in stabilizing thrombi, and in arteriosclerosis and vascular remodeling. The signaling mechanisms leading to secretion have not been well defined. We have shown previously that cGMP-dependent protein kinase (PKG) plays a stimulatory role in platelet activation via the glycoprotein Ib-IX pathway. Here we show that PKG also plays an important stimulatory role in mediating aggregation-dependent platelet secretion and secretion-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 51 publications
6
53
0
Order By: Relevance
“…2), indicating that the primary role for NOS3 is to stimulate aggregationdependent platelet secretion. This is consistent with our data on the role of PKG in platelet secretion, indicating NOS3 is upstream of cGMP elevation and PKG activation in stimulating platelet secretion (30). Interestingly, a previous study indicated a role for NOS3 in insulininduced secretion of ATP and other vasodilator compounds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2), indicating that the primary role for NOS3 is to stimulate aggregationdependent platelet secretion. This is consistent with our data on the role of PKG in platelet secretion, indicating NOS3 is upstream of cGMP elevation and PKG activation in stimulating platelet secretion (30). Interestingly, a previous study indicated a role for NOS3 in insulininduced secretion of ATP and other vasodilator compounds.…”
Section: Discussionsupporting
confidence: 93%
“…cGMP stimulates several intracellular molecules, including PKG, cGMP-gated ion channel, and cGMP-regulated phosphodiesterases. Although it was believed that cGMP inhibits platelet activation by activating PKG, we have shown that PKG in fact plays an important stimulatory role in platelet activation (28,30,36), as PKG knock-out mouse platelets and PKG inhibitor-treated human platelets showed significantly reduced platelet aggregation in response to low dose agonists including soluble agonists thrombin, thromboxane A2, and adhesive proteins VWF and collagen. On the other hand, the inhibitory effects of NO donors and cGMP analogs on human platelets were reversed by inhibitors of cAMPdependent protein kinase (37) and adenylyl cyclase (38), indicating that these effects require elevation of cAMP, possibly induced by inhibition of cGMP-regulated phosphodiesterase 3 (31).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recent investigations proposed the sequential activation of p38 and ERK pathways by PKG 7,8,21 as a novel "roadway" to ␣IIb␤3 activation. 22 These studies with human platelets again heavily relied on the use and functional effects of PKG inhibitors that (similar to p38 inhibitors) need to be used with caution and proper controls including nucleotides inactive with respect to PKG Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Data from a preliminary study of neutrophil degranulation suggest that release of enzymes from all three major classes of neutrophil granules is subjected to inhibition of PKG and PI3K (Table I). Recently, Li et al (52) reported that PKG plays an important role in aggregation-dependent release of dense granule and ␣-granule in platelets. Thus, PKG may be involved in degranulation triggered by multiple extracellular stimuli in different types of cells.…”
Section: Discussionmentioning
confidence: 99%